2010
DOI: 10.1007/s11125-010-9173-3
|View full text |Cite
|
Sign up to set email alerts
|

The politics of educational transfer and policymaking in Egypt

Abstract: For the past two centuries, western modern education has informed education policies and practices in Egypt. However, few researchers have analyzed the historical or current politics of educational transfer in this country. This article investigates the ways in which foreign transfer has influenced Egyptian education, both historically and currently. It concludes that current Egyptian education is a product of inappropriately adapted foreign transfers coupled with domestic interest in spreading education with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Though in this reform experience, that falls within the first two stages of Bybee's (2010) model of STEM reform, challenges were identified that might cripple the sustaining phase of the STEM initiative (Bybee, 2010). This is particularly the case when considering Fullan's tri-level and the different forms of resistance to change within the Egyptian bureaucratic institutions (Ibrahim, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though in this reform experience, that falls within the first two stages of Bybee's (2010) model of STEM reform, challenges were identified that might cripple the sustaining phase of the STEM initiative (Bybee, 2010). This is particularly the case when considering Fullan's tri-level and the different forms of resistance to change within the Egyptian bureaucratic institutions (Ibrahim, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Although expanding this change to the larger context of the Egyptian education system was one of the tasks of the ECASE and the MoE, the teachers grabbed the opportunity to provide leadership and to help teachers in their schools and teachers in the new STEM schools to join them in this transformative process by providing professional development for their new colleagues. However, sustaining this change (Bybee, 2010), despite these transformative efforts, is in jeopardy due to the resistance to change at the bureaucratic levels in the Egyptian education system (Ibrahim, 2010;Shawky, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Egypt's education system is largely a product of an interaction between its historical, social, and political developmentincluding foreign educational systems transfersas well as the more recent internal reforms (Ibrahim, 2010). The 1990s witnessed vast international discussions on education, which affected the local reform landscape.…”
Section: Context Of Education Reform In Egyptmentioning
confidence: 99%
“…For more analysis on the role of regional agencies such as CARICOM (spell out acronym here), see Jules, 2010 and It would be useful to further understand successful cases of implementation, particularly in developing countries. While there are notable cases of borrowing between industrialized countries and 'North-South' borrowing in countries such as South Africa, Mongolia, Egypt and India among others (see Jansen, 2004, Spreen, 2004, Vavrus, 2004, Steiner-Khamsi and Stolpe, 2006, Ibrahim, 2010, Mukhopadhyay& Sriprakash, 2011, little has been written on the South-South approach. Two cases have been identified: Colombia-Brazil (see Luschei, 2004) and international influences on post-conflict Rwanda (see Schweisfurth, 2006).…”
mentioning
confidence: 99%